As repercussões das intervenções profissionais na dinâmica de vida das mulheres vítimas de violência doméstica (2012)
AbstractThis article aims to analyze and understand the impact of actions developed in the NGO SOS Ação Mulher e Família and Centro de Referência e Apoio à Mulher – CEAMO, attention services from Campinas, SP/Brazil, in the life dynamics of women victims of domestic violence. This study attempts to show the interventions developed and applied by professionals from both institutions as strategies to break the violence cycle. The methodology used was qualitative research through focus group and individual interviews, with a group of five women who had previously used the SOS service, and interviews conducted with four women who had previously used the CEAMO service. Results showed that the interventions performed by attention service professionals reflected positively in the dynamics of women’s lives by transforming their reality and helping them break the cycle of violence.